A novel mitochondrial-targeting fluorescent probe based on 1, 4-dihydropyridine to visualize and monitor the viscosity of live cells and mice in vivo. Issue 37 (1st September 2021) - Xue, Longqi; Lv, Jialin; Li, Ronghang; Xinyu Wang,; Li, Yapeng; Du, Jianshi; Qi, Shaolong; Yang, Qingbiao; Shan, Yaming; Li, Yaoxian
Abstract : Cell viscosity is related to some diseases, such as diabetes, atherosclerosis, and Alzheimer's disease. Abstract : Cell viscosity is related to some diseases, such as diabetes, atherosclerosis, and Alzheimer's disease. These diseases can cause abnormal viscosity of the cell mitochondrial matrix. 1, 4-Dihydropyridine (DHP) is an important organic compound with biological activity and is widely used in drug research. However, there are few studies on its optical properties, especially in the design of viscous fluorescent probes. In this study, a fluorescent probe for viscosity detection using 1, 4-dihydropyridine as the fluorophore and indole iodide salt as the recognition group was designed and synthesized. The probe has the advantages of a deep-red emission, low cytotoxicity, good biocompatibility and excellent anti-interference ability. In addition, the probe also has the ability to target mitochondria and has been successfully applied to the detection of the viscosity response of HeLa cells and living mice, and has good clinical application potential.